1999
DOI: 10.1016/s0016-7037(99)00049-6
|View full text |Cite
|
Sign up to set email alerts
|

A study of oxygen isotopic fractionation during bio-induced calcite precipitation in eutrophic Baldeggersee, Switzerland

Abstract: Abstract-In order to better understand environmental factors controlling oxygen isotope shifts in autochthonous lacustrine carbonate sequences, we undertook an extensive one-year study (March, 1995 to February, 1996 of water-column chemistry and daily sediment trap material from a small lake in Central Switzerland. Comparisons between calculated equilibrium isotope values, using the fractionation equation of Friedman and O'Neil (1977) and measured oxygen isotope ratios of calcite in the sediment-traps revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 22 publications
8
40
0
Order By: Relevance
“…Evaporation, itself governed by temperature and relative humidity, strongly controls the depletion in the light oxygen isotope 16 O in the water phase. Changes in temperature, rainfall sources, riverine influx, and groundwater input are retained in the oxygen isotope ratios of carbonates (δ 18 O carb ) which precipitate from lake water (e.g., Turner et al 1983;Talbot 1990;Teranes et al 1999;Lamb et al 2000;Schwalb & Dean 2002;Leng & Marshall 2004;Yansa et al 2007;Davis et al 2009;Deocampo 2010;Kent-Corson et al 2010 (Leng & Marshall 2004). Lacustrine carbonate oxygen isotope records have been also used in isotopebased paleoelevation models exploiting the systematic relationship between oxygen isotopes in precipitation and surface elevation (e.g., Currie et al 2005;Garzione et al 2008;Mix et al 2011;Campani et al 2012).…”
Section: Stable Oxygen Isotope Geochemistrymentioning
confidence: 99%
“…Evaporation, itself governed by temperature and relative humidity, strongly controls the depletion in the light oxygen isotope 16 O in the water phase. Changes in temperature, rainfall sources, riverine influx, and groundwater input are retained in the oxygen isotope ratios of carbonates (δ 18 O carb ) which precipitate from lake water (e.g., Turner et al 1983;Talbot 1990;Teranes et al 1999;Lamb et al 2000;Schwalb & Dean 2002;Leng & Marshall 2004;Yansa et al 2007;Davis et al 2009;Deocampo 2010;Kent-Corson et al 2010 (Leng & Marshall 2004). Lacustrine carbonate oxygen isotope records have been also used in isotopebased paleoelevation models exploiting the systematic relationship between oxygen isotopes in precipitation and surface elevation (e.g., Currie et al 2005;Garzione et al 2008;Mix et al 2011;Campani et al 2012).…”
Section: Stable Oxygen Isotope Geochemistrymentioning
confidence: 99%
“…Stable isotopes in biogenic and authigenic carbonates were used for palaeoclimatic reconstructions for decades, mainly in the marine environment (Wefer et al 1999), but also from speleothems (e.g., McDermott 2004; Fairchild et al 2006), and as well from lake sediments (e.g., Stuiver 1970;Fronval et al 1995;Teranes et al 1999a).…”
Section: Introductionmentioning
confidence: 99%
“…Fronval et al (1995) reported isotopically depleted oxygen isotope values relative to calculated equilibrium values in Lake Arresø, Denmark, which are possibly caused by a high level of eutrophication in this lake. Teranes et al (1999a) showed that calcites of Baldeggersee, Switzerland, precipitated in isotopic equilibrium during summer only. This was also reported for Lake Neuchâtel, Switzerland (Filippi et al 1998).…”
mentioning
confidence: 99%
“…The observed wide range of isotope values clearly indicate that temperature-dependent isotope fractionation (e.g. Teranes et al 1999) played a minor role.…”
Section: Proxy Data and Related Hypotheses In South-eastern Patagoniamentioning
confidence: 91%